A concepção de homem na filosofia de Éric Weil - NASCIMENTO, David Mendonça do (2023)
This dissertation deals with the conception of man in Éric Weil's philosophy from the perspective of Introduction of the Logic of Philosophy, in the first section entitled Reflection on Philosophy, subdivide into two parts Man as Reason and Man as Violence. questioning the Western classical concept of man as a rational animal he seeks definition in the sense human. He understands that the concept of man must not be given to define him, but to realize it, that is, man is an ideal to be achieved through free choice by reason. O man is constituted of the opposition between reason and violence: he is neither wholly reason nor utterly violence; nor only rational (coherence, sense), nor only animal (natural, the moral); neither naturally good nor naturally bad, but, in this sense, in the coexistence of human community, through the exercise of language, a reasonable being, capable of morality, to elaborate rules that distinguish what is licit from illicit, moral from immoral. The individual to be a man one must be reasonable. In view of this, he classifies men into two general groups: homo faber and homo theoreticus. Homo faber is the type who seeks his contentment in praxis. and find the ephemeral satisfactions. Homo theoreticus is the type that seeks his contentment in reason, in theory, in the vision of the unity of totality. These concepts mark the analysis of the man as a being of action and speech, who acts and speaks, speaks and acts; reasonable action producer (attitudes) and reasonable language (categories). His speech produces meaning, coherence and guidance their existence and actions in the world. Your lifestyle, values ​​and ideals form your attitude in the world. The coherent discourse that organizes this set of elements forms the category. O man is negativity, that is, he has within himself a discontent that leads him to say no to your world and yourself. By becoming aware of its condition in the data, it seeks to transform his reality to his satisfaction, ceasing to be simple homo sapiens becomes homo faber, being-craftsman who manufactures himself as he seeks to define himself by transforming the given. However, when fulfilling his satisfactions, he finds that he is still dissatisfied. By understanding this, he goes on to deny his own negativity to find contentment solely in reason. It is when he makes the transition from homo faber to homo theoreticus. Man is contradiction, being in an act of realization, however it is reason-thinking and reason-thought, freedom that self-determines, that by choosing coherence and meaning, it diminishes the violence within. The question that expresses the opposition between homo faber and homo theoreticus, which is also the question about the meaning of human existence, is about the role of philosophy: man must philosophize to live or live to philosophize?